Hubungan Komunikasi Interpersonal dengan Kepuasan Kerja Karyawan PT. PLN (Persero) UP3 Pematang Siantar - Suci Lumban Sakinah Tobing; Khairuddin Khairuddin (Universitas Medan Area, 2023)
This study purpose to determine the correlation between interpersonal communication with employee job satisfaction. Interpersonal communication is the communication process of between two or more people through verbal or non-verbal methods. Job satisfaction is measure of worker's positive feelings derives from their job, which is perceived from the comparison between actual work results and expected results. The population in this study is all employees of PT. PLN (Persero) UP3 Pematang Siantar, totaling 63 samples, used a total sampling method. The measuring instrument used is the Interpersonal Communication scale and the Job Satisfaction scale by using Likert scale. The data processing in this study used the Product Moment correlation method by Pearson. The results showed a correlation of rxy =0.488 with p = 0,000 (p0,05), means that there is a significant positive correlation between Interpersonal Communication and Job Satisfaction. It means that the better the Interpersonal Communication, the higher the Job Satisfaction. Interpersonal Communication provides an effective contribution of 23.8%. while the remaining other factors that influence in this study that are not visible, that are opportunities for advancement, job security, salary, company and management, supervision (supervise), intrinsic factors of work, working conditions, social aspects of work and facilities.